Study of Guillain-Barre syndrome etiology in Pakistani patients - Iqbal , Rashid; Muhammad Javaid Asad; Saima Siddiqi; Raja Tahir Mahmood; Muhamamd Baseer Shah (Journal of the Pakistan Medical Association, 2021)
Objective: To examine clinical features, biochemical markers, demographic features, antecedent infections, frequency and treatment strategies. Methods: This case-control study was conducted at Pakistan Institute of Medical Sciences (PIMS), Islamabad, Pakistan and District Headquarters Hospital (DHQ), Rawalpindi, Pakistan from 2018 to 2020. Ninety consecutive patients of Guillain-Barré syndrome (GBS) and 77 healthy controls were enrolled. Patients were diagnosed by clinical presentation, Nerve conduction study (NCS), Electromyography (EMG), Cerebrospinal fluid analysis (CSF) and biochemical profile. Data was analyzed on IBM SPSS version 23. Results: Symmetrical ascending weakness was the striking clinical feature. Mean age was 40.20±14.90 years and male to female ratio was 2.1:1. Acute inflammatory demyelinating polyneuropathy (AIDP) was found to be the most common electrophysiological variant of GBS (46%). There was considerable difference in Interleukin-17(IL-17) levels between GBS patients 23.12 ± 3.41 pg/ml and healthy controls 8.82 ± 2.49. Mean IL-17 level was markedly increased in GBS patients, P=0.006, P<0.05. Gastrointestinal infection was the most common preceding infection (56.66%). Mean CSF protein was 100.83 g/dl with ± 51.32 standard deviation and albumio cytologic dissociation (ACD) was different in all four variants of GBS, P= 0.005. Conclusion: GBS was presented by all ages. Males were more affected than females. About two third of GBS patients showed an antecedent infection before GBS onset. Increased levels of cytokine (IL-17) showed involvement of autoimmunity. ACD differentiated it from poliomyelitis. Plasmapheresis and intravenous immunoglobulin (IVIG) therapy were used to treat patients. Key words: Guillain-Barré Syndrome; cerebrospinal fluid; albuminocytologic dissociation; nerve conduction studies; variants; electromyography Continuous....